Factors of Learning Difficulties of Students in Science Subjects for Class VII A And VII B at SMP Negeri 19 Palu - Nanda Sudin Djafar; Lilies N. Tangge; Musdalifah Nurdin (CV. Dharma Samakta Edukhatulistiwa, 2024)
This study aims to describe the factors of learning difficulties in science subjects at SMP Negeri 19 Palu. This research used a qualitative research method. The data collection technique used was a questionnaire on factors of student learning difficulties. The results show that internal factors affected 36% of students who did not experience difficulties and 64% of students who experienced learning difficulties. Meanwhile, external factors affected 46% of students who did not experience learning difficulties and 54% of students who experienced learning difficulties. It can be concluded that there are factors of learning difficulties in science subjects at SMP Negeri 19 Palu.